Barriers to and Facilitators of Early Hearing Detection and Intervention in the United States: A Systematic Review. Issue 3 (29th December 2022) - Findlen, Ursula M.; Davenport, Carrie A.; Cadieux, Jamie; Gehred, Alison; Frush Holt, Rachael; Vaughn, Lisa M.; Houston, Derek; Hunter, Lisa L.
Abstract : Objectives: Early hearing detection and intervention (EHDI) is guided by the 1-3-6 approach: screening by one month, diagnosis by 3 mo, and early intervention (EI) enrollment by 6 mo. Although screening rates remain high, successful diagnosis and EI–enrollment lag in comparison. The aim of this systematic review is to critically examine and synthesize the barriers to and facilitators of EHDI that exist for families, as they navigate the journey of congenital hearing loss diagnosis and management in the United States. Understanding barriers across each and all stages is necessary for EHDI stakeholders to develop and test novel approaches which will effectively reduce barriers to early hearing healthcare. Design: A systematic literature search was completed in May and August 2021 for empirical articles focusing on screening, diagnosis, and EI of children with hearing loss. Two independent reviewers completed title and abstract screening, full-text review, data extraction, and quality assessments with a third independent reviewer establishing consensus at each stage. Data synthesis was completed using the Framework Analysis approach to categorize articles into EHDI journey timepoints and individual/family-level factors versus system-level factors. Results: Sixty-two studies were included in the narrative synthesis. Results revealed that both individual/family-level (e.g., economic stability, medical status of the infant including middle ear involvement) and system-level barriers (e.g., system-service capacity, provider knowledge, and program quality) hinder timely diagnosis and EI for congenital hearing loss. Specific social determinants of health were noted as barriers to effective EHDI; however, system-level facilitators such as care coordination, colocation of services, and family support programs have been shown to mitigate the negative impact of those sociodemographic factors. Conclusions: Many barriers exist for families to obtain appropriate and timely EHDI for their children, but system-level changes could facilitate the process and contribute to long-term outcomes improvement. Limitations of this study include limited generalizability due to the heterogeneity of EHDI programs and an inability to ascertain factor interactions.